Microbial connectivity and sorting in a High Arctic watershed. Issue 12 (December 2018) - Comte, Jérôme; Culley, Alexander; Lovejoy, Connie; Vincent, Warwick
Abstract Aquatic ecosystems in the High Arctic are facing unprecedented changes as a result of global warming effects on the cryosphere. Snow pack is a central feature of northern landscapes, but the snow microbiome and its microbial connectivity to adjacent and downstream habitats have been little explored. To evaluate these aspects, we sampled along a hydrologic continuum at Ward Hunt Lake (latitude 83°N) in the Canadian High Arctic, from snow banks, water tracks in the permafrost catchment, the upper and lower strata of the lake, and the lake outlet and its coastal marine mixing zone. The microbial communities were analyzed by high-throughput sequencing of 16 and 18S rRNA to determine the composition of potentially active Bacteria, Archaea and microbial Eukarya. Each habitat had distinct microbial assemblages, with highest species richness in the subsurface water tracks that connected the melting snow to the lake. However, up to 30% of phylotypes were shared along the hydrologic continuum, showing that many taxa originating from the snow can remain in the active fraction of downstream microbiomes. The results imply that changes in snowfall associated with climate warming will affect microbial community structure throughout all spatially connected habitats within snow-fed polar ecosystems.